Re-conceptualizing Child Victim Rights: A Normative and Comparative Analysis of Victim Impact Statement in Indonesia’s Juvenile Justice System - Aprilianda, Nurini; Maharani, Febrianika; A. Kadir, Nadhilah; Ferdian, Ardi; Solehuddin, Solehuddin (Jambura Law Review, 2025)
In Indonesia, the participation of child victims in criminal proceedings remains highly constrained. Courtroom questioning still centers on extracting material facts, while the psychological, emotional, and developmental harm inflicted by crime receives scant judicial attention. This article analyzes whether embedding Victim Impact Statements (VIS) in juvenile proceedings could correct that imbalance. Using a normative‑juridical methodology that combines statutory interpretation, doctrinal analysis, and comparative research, the study reviews VIS implementation in the United States, Canada, England and Wales, and South Africa, and tests its coherence with Indonesia’s Law No. 11 of 2012 on the Juvenile Criminal Justice System (JCJS Law). The comparative findings demonstrate that VIS offer a structured, low‑cost channel for children and their guardians to describe the multidimensional fallout of crime, thereby enriching judges’ sentencing rationales and promoting restorative outcomes. Evaluations in those jurisdictions also show that VIS boost victim satisfaction and enhance perceived legitimacy of the courts. To harness these benefits, the paper proposes amending the JCJS Law to require judges to solicit and consider VIS in every juvenile case involving a child victim. Procedural safeguards-mandatory psychological assistance, child‑friendly language,  closed‑court delivery options, and trauma‑informed questioning are recommended to prevent secondary victimization.Codifying these protections would close a normative gap, align national law with both the U.N. Convention on the Rights of the Child and Sustainable Development Goal 16 on justice, and support Indonesia’s broader commitment to child‑centered jurisprudence. Ultimately, institutionalizing VIS can transform victims from passive evidence providers into active rights holders whose voices shape fair, balanced, and developmentally sensitive judicial decisions.